Integrating Network Pharmacology and Molecular Docking to Identify the Active Substances and Mechanisms of Chrysanthemum Against Dry Eye (Global Journal of Medical Research, 2024)
Background Dry eye is the most common ocular surface disease and is widely treated with chrysanthemum an herbal medicine known for its anti-inflammatory mechanism However the active ingredients potential targets and pathways of chrysanthemum in treating dry eye have not been clearly identified Objective The objective of this study is to explore the bioactive components and potential mechanism of chrysanthemum on dry eye using network pharmacology and molecular docking Methods We used the TCMSP database to search and screen the active ingredients of chrysanthemum and their related targets Targets associated with dry eye were collected and screened using the Genecards database
Keywords: chrysanthemum; dry eye; chinese medicine; network pharmacology; molecular docking